Data dreams and the distrust of discretion - Pors, Anja Svejgaard; Pedersen, Kirstine Zinck; Kirkegaard, Line (Politica, 2023)
How is the dream of artificial intelligence and the potentiality of data shaped among managers in the public administration? What roles are assigned to the frontline employee in data-driven welfare? Based on observations of municipal managers and consultants, the article examines a project group’s attempt to introduce artificial intelligence in municipal employment efforts. The distrust in the frontline employee mimics research traditions in studies of management and professions. In alignment with these research traditions, the data dream problematizes how human experience distorts political goals, impairs organizational value creation, is driven by individual coping strategies or professional interest and therefore does not provide appropriate welfare service.